2013
DOI: 10.1299/jmmp.7.273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Lead and Yttrium Addition on the Microstructure and Mechanical Properties of AZ91 Magnesium Alloy

Abstract: This article reports the effect of individual additions of Pb and Y on the precipitation sequence and mechanical properties of AZ91 magnesium alloy. Discontinuous phase is greatly suppressed with Pb addition, since Pb in solid solution effectively reduces the diffusion of Al and Mg atoms, which is significant for the formation and growth of discontinuous phases. Suppression of the discontinuous phase is also obtained with Y addition but in lesser extent. Besides, addition of Y introduces Al 2 Y phase which sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Compared with the as-cast Mg97Zn1Y2 alloy, after adding Pb into the Mg97Zn1Y2 alloy, a new particle phase appeared at the grain boundary and its volume fraction increased with increasing Pb content. The solid solution can be easily formed due to the high solid solubility of Pb in Mg. Pb was added to the Mg alloy, which helped to refi ne the microstructure of the alloy and changed the morphology of the secondary phase, thereby improving Research & Development properties of the alloy [21] . During the solidification process of the alloy, Pb concentration in the liquid phase was higher than that in the solid phase due to the diff erence concentration around the solid-liquid interface.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the as-cast Mg97Zn1Y2 alloy, after adding Pb into the Mg97Zn1Y2 alloy, a new particle phase appeared at the grain boundary and its volume fraction increased with increasing Pb content. The solid solution can be easily formed due to the high solid solubility of Pb in Mg. Pb was added to the Mg alloy, which helped to refi ne the microstructure of the alloy and changed the morphology of the secondary phase, thereby improving Research & Development properties of the alloy [21] . During the solidification process of the alloy, Pb concentration in the liquid phase was higher than that in the solid phase due to the diff erence concentration around the solid-liquid interface.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al, 2019) form. Researchers have observed that the modification of β-Mg 17 Al 12 in Mg-Al-Y alloys is responsible for improved mechanical properties (Boby et al, 2013;Cai et al, 2018;Kashefi & Mahmudi, 2012;S.-R. Wang et al, 2009). Previous work (Korgiopoulos & Pekguleryuz, 2020) by the authors has shown that the refinement of β-Mg 17 Al 12 improves the ductility of Mg-6Al cast alloys at trace Y additions.…”
Section: Introductionmentioning
confidence: 99%